2020
DOI: 10.35848/1347-4065/abba10
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ni-doped stainless steel thin films on metal to prevent hydrogen entry via sputter deposition with a powder target

Abstract: Nickel-doped stainless steel thin films with high hydrogen-entry resistance were prepared on a metal and Si surface via sputter deposition. For this, mixed nickel oxide (NiO) and stainless steel (SUS304) powders were used as the sputtering target. The experimental results indicated that nickel-doped stainless steel thin films could successfully be prepared both on the stainless steel and Si substrate surface. XPS measurements demonstrated that the deposition rate was dependent on the processing conditions such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The spectra of the film surface included peaks from Ni (Ni 2p 3/2 : 852 eV and Ni 2p 1/2 : 870 eV) and Fe (Fe 2p 3/2 : 707 eV). 29,30) Chemical shifts were observed for both peaks and there was splitting of the Ni 2p 3/2 peak, which confirmed that the prepared films were in the oxide form. Figure 5 shows the Ni and Fe concentration ratio in the film (150 W RF power) as a function of the mass ratio of NiO and SUS304 combined in the mixed powder target.…”
Section: Dependence Of the Film Qualities On The Powder Target Mixturementioning
confidence: 53%
“…The spectra of the film surface included peaks from Ni (Ni 2p 3/2 : 852 eV and Ni 2p 1/2 : 870 eV) and Fe (Fe 2p 3/2 : 707 eV). 29,30) Chemical shifts were observed for both peaks and there was splitting of the Ni 2p 3/2 peak, which confirmed that the prepared films were in the oxide form. Figure 5 shows the Ni and Fe concentration ratio in the film (150 W RF power) as a function of the mass ratio of NiO and SUS304 combined in the mixed powder target.…”
Section: Dependence Of the Film Qualities On The Powder Target Mixturementioning
confidence: 53%
“…As noted above, the In X-ray diffraction peak was not observed for the 1:1:1 mixture, and only appeared in the 2:1:1 mixture. Previously, for Sn-doped SiO 2 thin films prepared using targets containing Sn and SiO 2 powders [21][22][23][24][25], the Sn/SiO 2 ratio was difficult to control. This may have been because of the much lower melting temperature of Sn (504 K) compared with that of SiO 2 (1 923 K) [26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…It is possible to obtain a few samples with different doping densities during one technological cycle [16]. This approach was also used to fabricate functional thin films containing multiple elements [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. For example, bismuth iron garnet (Bi 3 Fe 5 O 12 ) films used for magneto-optics were fabricated by sputter deposition of mixed bismuth (Bi) and iron (Fe) powder targets.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, plasma processes using multielement powder targets have been used to prepare functional multielement thin films in single-step processes [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . In this process, several kinds of powder can be mixed and placed in a target holder in a vacuum chamber.…”
Section: Introductionmentioning
confidence: 99%